EFFECTS OF VALUE ADDED TAX INCREASE ON HOUSEHOLDS’ WELFARE IN SOUTH AFRICA - Bongani Lawrence Kwebulane; Abayomi Samuel Oyekale (Acta Economica, 2025)
The South Africa’s Value Added Tax increased from 14% to 15% on the 1st of April 2018 because of the compelling need to avoid budget deficits. Value Added Tax increment always leads to consumer price increase with some adverse impacts on consumers’ purchasing power. This study evaluated the welfare effects of commodity price changes after the Value Added Tax increase on South African families. The data were from the National Income Dynamics Survey 2018 and the South African Consumer Price Indexes (2017/18 and 2018/19). Price elasticities were obtained from the Quadratic Almost Ideal Demand System Model and the impact of commodity price fluctuations in terms of Compensating Variation were then calculated using price elasticities. The study’s conclusions provide an essential basis for an empirical examination to pinpoint the effects on welfare. The paper recommends that instead of having a uniform VAT standard rate, luxury goods should be subject to a higher VAT rate such as expensive watches, yachts and cars. Due to the large percentage of luxury goods being imported, domestic demand may not be negatively impacted, and the balance of payments may even slightly improve. Also, the study endorses that the list of items with a zero rating be expanded to include more products that the poor purchase more frequently, such as all types of bread, soaps, candles and items connected to education (such as school uniforms). Additionally, these findings are a part of a bigger investigation into quantitative evaluations of policy alternatives to guide the nation’s VAT reform.